Not My Job, I Do Not Want to Do It: The Effect of Illegitimate Tasks on Work Disengagement - Zong, Shuwei; Han, Yi; Li, Min (Frontiers in Psychology, 2022)
As a prevalent source of work stress, illegitimate tasks offend employees’ professional identity and threaten individual self-view, then create many negative organizational outcomes. However, current studies have paid inadequate attention to the impact of illegitimate tasks on work disengagement and its influencing path, failing to comprehensively identify the negative effects of illegitimate tasks. Based on stress-as-offense-to-self (SOS) theory and ego depletion theory, the influencing path of illegitimate tasks on work disengagement was explored, and coworker emotional support and leisure crafting were introduced to explore the intervention conditions on the impact of illegitimate tasks. By analyzing data from a survey of 260 employees, this study reveals the following findings: illegitimate tasks have a significantly positive impact on work disengagement; ego depletion fully transmits the positive impact of illegitimate tasks on work disengagement; coworker emotional support and leisure crafting not only attenuate the effect of illegitimate tasks on ego depletion, but also negatively moderate the indirect effect of illegitimate tasks on work disengagement through ego depletion.